Razpoznavna struktura mesta - Dimitrovska Andrews, Kaliopa (Urbani izziv, 2001)
In view of the ongoing societal changes, views on urban development are changing as well. Recognisable urban structure is understood as a value in allphysical development concepts. Therefore when the physical development concept of Ljubljana was being prepared, special emphasis was given to strengthening the cities identity. The article presents ideas about enhancing the identity of urban spaces, environments and heritage. On this basis a methodology for identifying urban spaces was defined and proposals given for the integration of recognisable structures into the physical development plan.Criteria for their sustainable development conclude the article.
Keywords: Ljubljana; mesta; mestni predeli; mestni prostor; morfologija naselij; raba prostora; struktura